Modelling Social Psychological Support within the System of Inclusive Higher Education: The Experience of Novosibirsk State Technical University - Osmuk, L.A.; Degtyaryova, V.V.; Zhdanova, I.V. (Psihologičeskaâ nauka i obrazovanie, 2017)
The article considers the problem of modelling the specific structure of social psychological support of students with disabilities in the context of inclusive education development. The article reveals the functions, system character and means of application of this structure in the course of realization of professional and educational paths. The authors analyze different models of social psychological support in the university and address the question of the efficiency of these models and their compliance with resources and demands of the university. The problem of the optimal model is considered. The authors suggest outsourcing as a solution for universities with limited number of assistive resources and small amount of students with disabilities. Developing the model implies taking into account perceptions and assessments of social psychological support in students with disabilities in each step of their professional path. В статье определяется проблема моделирования специфической структуры социально-психологического сопровождения студентов с инвалидностью в контексте развития системы инклюзивного образования. Раскрываются ее функции, системный характер, использование в процессе реализации профессионально-образовательной траектории. Анализируются различные модели социально-психологического сопровождения учащихся с инвалидностью и ограниченными возможностями здоровья в вузе, поднимается вопрос об эффективности таких моделей и их соответствии возможностям и потребностям вуза. Рассматривается проблема оптимальной модели. В качестве выхода из ситуации для университетов с ограниченным количеством ассистивных ресурсов и небольшим количеством студентов с инвалидностью предлагается аутсорсинг. При разработке модели учитыва- ется восприятие и оценка социально-психологического сопровождения студентом с инвалидностью на каждом этапе прохождения профессиональной траектории.